Color image encryption with semi-tensor product compressive sensing and quaternion discrete fractional Krawtchouk transform - Yu, Wen-Jun; Ding, Hong-Xing; Fang, Zhong-Hua; Gong, Li-Hua (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
A color image encryption scheme is investigated by integrating the semi-tensor product compressive sensing (STP-CS) with the quaternion discrete fractional Krawtchouk transform (QDFrKT). To process the color components of plaintext image as a whole, the discrete fractional Krawtchouk transform (DFrKT) is popularized into the quaternion domain and the color image is secured by the QDFrKT. The image matrices are compressed with the discrete wavelet transform (DWT) and the STP measurement matrix. Then the compressed matrices represented by quaternion algebra are re-encrypted by the double random phase encoding and the quaternion DFrKT. Subsequently, the nonlinear hyperchaotic Lorenz system is applied to pixel diffusion to obtain the encrypted image. The proposed reconstruction algorithm based on the grouping iterative reweighted least squares (GIRLS) can resume the decryption image with high precision. The efficiency, security and robustness of the image compression encryption algorithm for color images are evaluated.
Optica Applicata, Vol. 54, 2024, nr 3, s. 435-453
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; image encryption; chaotic system; quaternion discrete fractional Krawtchouk transform; compressive sensing; semi-tensor product